Contributions of Jamaludheen Musliyar: A study from Malappuram District - Muhammed Atheeque PP AND M Thavamani (International Journal of Multidisciplinary Research and Development, 2016)
Reformation means making changes to something with the intention of setting it back on the right path. The aim of all reformers is to revive the society and empower the community. Whether it is social reformation or religious reformation, all kind of improvement in the world have been done with the influence of reform leaders only. Difference between religious reformers and social reformers is religious reformers give more important to religious matters but social reform leaders give the Conscious on every part of society. That’s why study of reformers will help to create new reformers or bring the new ideas to the society. Keeping in this view the present study attempted to understand Jamaludheen Musliyar (known as Usthad) as a Social reformer. It studies various contributions of Usthad in the field of education, charity, orphan care, religious awareness and social development. It also studies influence of Usthad on people from beneficiaries’ perspective. Five focus group discussions have been conducted for the data collection.